Impact of nursing systematic education on disease knowledge and self-care at a heart failure clinic in Brazil: prospective an interventional study - Eneida Rejane Rabelo; Graziella Badin Aliti; Fernanda Bandeira Domingues; Karen Brasil Ruschel; Anelise Oliveira Brun (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
The aim of this prospective and experimental study was to evaluate the impact of nursing systematic education on disease knowledge and self-care at a Heart Failure Clinic in Brazil. Prior to the nurse's appointment, all patients answered a structured questionnaire concerning the knowledge of the disease and self-care. After 4 appointments, the same patients answered the same questionnaire. This present study suggests that systematic education with nurses increase the knowledge about the disease and self-care. This approach together with others strategies could decrease decompensation episodes and consequently improve quality of life for heart failure patients.